Professional Work for Nothing: Software Commercialization and "An Open Letter to Hobbyists". - Driscoll, Kevin (Information & Culture, 2015)
In 1975 Bill Gates published "An Open Letter to Hobbyists" in response to unauthorized duplication of Microsoft software. The letter appeared in numerous hobby magazines and club newsletters, sparking a dialogue among contemporary hobbyist readers, many of whom had not yet seriously considered the ethical and economic dimensions of commercial software. In the 1980s, histories of personal computing published in the popular press preserved a memory of the open letter that was later taken up by advocates of the free and open-source software movement. As the open letter traveled through each of these discursive contexts, it enabled enthusiasts and entrepreneurs alike to think about the problems of ownership, authorship, labor, and value brought about by software commercialization.